Residual Spinal Cord Compression Following Hemilaminectomy and Mini-Hemilaminectomy in Dogs: A Prospective Randomized Study - Svensson, Gustaf; Simonsson, Ulrika S. H.; Danielsson, Fredrik; Schwarz, Tobias (Frontiers in Veterinary Science, 2017)
Abstract The aim of this study was to compare the reduction of spinal cord compression after surgical treatment of dogs with acute thoraco-lumbar intervertebral disc extrusion achieved using hemilaminectomy versus mini-hemilaminectomy techniques. This was a prospective randomized study with client owned dogs presented with acute intervertebral disc extrusion that were allocated to surgical treatment using hemilaminectomy (n=15) or mini-hemilaminectomy (n=15) techniques. Plain and intravenous (IV)-contrast computed tomography (CT) was performed pre- and postoperatively. The preoperative minimal cross-sectional dimension of the spinal cord (MDSCpre) and the postoperative minimal cross-sectional dimension of the spinal cord (MDSCpost) were measured at the level of greatest compression. The minimal diameter of the uncompressed spinal cord was measured in a similar way both pre (MDUSCpre) and postoperatively (MDUSCpost). Dogs in the mini-hemilaminectomy group had significantly greater reduction of compression (RC) (p<0.01) after surgery compared to dogs in the hemilaminectomy group. The mean RC in the hemilaminectomy group was 34.6 % and in the mini-hemilaminectomy group 62.6 %. Our results showed a significantly greater reduction of spinal cord compression for mini-hemilaminectomy compared to hemilaminectomy. Additionally, mini-hemilaminectomy could be a preferred method due to its minimal invasiveness and easier access to lateral fenestration.